2003
DOI: 10.1083/jcb.200212060
|View full text |Cite|
|
Sign up to set email alerts
|

Direct signaling by the BMP type II receptor via the cytoskeletal regulator LIMK1

Abstract: Bone morphogenetic proteins (BMPs) regulate multiple cellular processes, including cell differentiation and migration. Their signals are transduced by the kinase receptors BMPR-I and BMPR-II, leading to Smad transcription factor activation via BMPR-I. LIM kinase (LIMK) 1 is a key regulator of actin dynamics as it phosphorylates and inactivates cofilin, an actin depolymerizing factor. During a search for LIMK1-interacting proteins, we isolated clones encompassing the tail region of BMPR-II. Although the BMPR-II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
252
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(269 citation statements)
references
References 34 publications
11
252
1
5
Order By: Relevance
“…In addition, LIMK1 is concentrated to the microtubules in Wdr1 KO MEF cells and the disassembly of microtubules can partly rescue the phosphorylated Cofilin in these cells. Previous reports show that the PDZ domain is a cytoskeleton binding domain and the PDZ domain can localize LIMK1 to the microtubules (21,37,38). Thus, these results suggest that WDR1 might inhibit the binding of LIMK1 to microtubules and release LIMK1 to the cytoplasm to catalyze Cofilin phosphorylation, therefore regulating the binding of F-actin to Cofilin.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In addition, LIMK1 is concentrated to the microtubules in Wdr1 KO MEF cells and the disassembly of microtubules can partly rescue the phosphorylated Cofilin in these cells. Previous reports show that the PDZ domain is a cytoskeleton binding domain and the PDZ domain can localize LIMK1 to the microtubules (21,37,38). Thus, these results suggest that WDR1 might inhibit the binding of LIMK1 to microtubules and release LIMK1 to the cytoplasm to catalyze Cofilin phosphorylation, therefore regulating the binding of F-actin to Cofilin.…”
Section: Discussionmentioning
confidence: 58%
“…Previous reports showed that LIMK1 activity was inhibited by binding with BMP-RII (bone morphogenetic proteins receptor II) or microtubules (21,37,38). Because the LIMK1 antibody did not work well for immunostaining, LIMK1 with the Myc tag was overexpressed in control and Wdr1 KO MEF cells to examine whether WDR1 regulates LIMK1 by changing its localization.…”
Section: Wdr1 Regulates Phosphorylation Of Cofilin In a Dose-independmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the Smad pathway, however, these alternative pathways are activated by TGFb in a cell type dependent manner, and their biochemical links to the activated receptors are largely unknown. Exceptions are the epithelial polarity protein Par6 which is directly regulated by the TGFb type II receptor to control epithelial cell plasticity [36], and LIM kinase, which directly interacts with the BMP type II receptor to control actin cytoskeleton dynamics and dendrite formation [37,38].…”
Section: Tgfb Signaling Pathwaysmentioning
confidence: 99%
“…Because RhoA regulates the dynamics of tight junctions and the actin filaments that support the assembly and function of such junctions, its loss causes tight junction dissolution. On the BMP side, the long carboxyterminal tail of BMPRII recruits LIM kinase 1 (LIMK1), which remains inactive and thus is prohibited from phosphorylating cofilin, the inhibitor of actin polymerization (Foletta et al 2003). Because LIMK1 inactivates cofilin, the action of BMPRII promotes cofilin activity and limits actin polymerization.…”
Section: Signaling Via Smad and Non-smad Pathwaysmentioning
confidence: 99%